Динаміка надходження товарів у керамічній тарі на Білозерське поселення хори Ольвії (спроба кількісної оцінки) - Нємцев, С.О. (Археологія, 2014)
Подано результати розрахунків кількісних показників надходження об’єму товарів у керамічній тарі (за матеріалами її решток) на Білозерське поселення. Поданы результаты расчетов количественных показателей поступлений античного импорта в амфорах. Они вы полнены на основании анализа выборки ножек амфор с Белозерского поселения хоры Ольвии (iv — начало iii в. до н. э.). Объем анализируемой выборки — более 800 единиц — позволяет сделать статистически достоверные наблюдения и выводы. Расчеты выполнены для двух вариантов хронологической периодизации. Первый вариант учитывает страти графию поселения. Выделяются три фазы: 1) первая половина iv в.; 2) третья четверть iv в.; 3) последняя четверть iv — начало iii вв. до н. э. В третьей четверти iv в. до н. э. объем импорта значительно вырос по сравнению с первой половиной века на 158 %. В последней четверти iv — в начале iii вв. до н. э. поступления сократились и составили в сравнении с первой половиной века 82 %, с третьей четвертью — 52 %. Максимальный уровень по ступлений в этом случае приходится на третью четверть iv в. до н. э. Второй вариант ориентирован на качественные перемены, фиксируемые в составе центровэкспортеров в 330е гг. до н. э. Таким образом, выделяются два периода: поздняя классика и ранний эллинизм. В этом случае наблюдаются различия не в общем количестве поступлений, а лишь в качественном составе, то есть, в том, какую долю рынка занимает продукция центровэкспортеров при переходе от одной фазы к другой. Полученные данные при условии достаточного количества опубликованных наблюдений такого рода могут быть использованы для совершения следующего шага в изучении античной торговли в Северном Причерноморье. Им станет разработка экономикогеографического районирования, основанного на количественных показателях поступлений импорта. presented are the results of calculations of quantitative indexes of arrived ancient Greek import in amphorae. They are made based on the analysis of amphorae stems excerpts from Bilozerka settlement at Olbian chora (the 4th and the begin ning of the 3rd c. BC). The volume of excerpts analysed (more than 800 items) allow the author to make statistically reliable observations and conclusions. The calculations are made for two variants of chronological division into periods. in the first variant, the stratigraphy of the settlement is taken into consideration. The three phases are defined: 1) the first half of the 4th c.; 2) the third quarter of the 4th c.; 3) the last quarter of the 4th c. and the beginning of the 3rd c. BC. in the third quarter of the 4th c. BC, the import volume increased 158 % comparing to the first half of the century. at the last quarter of the 4th c. and the beginning of the 3rd c. BC the arrivals seized to 82 % comparing to the first half of the century and to 52 % comparing to its third quarter. The highest level of arrivals in this case falls to the third quarter of the 4th c. BC. The second variant is oriented to the qualitative changes recorded in the composition of centresexporters in the 330s BC. as a result, two periods are singled out: the Late Classical and the early hellenistic. in this case observed are the differences not in general number of arrivals, but only in qualitative composition, i.e. in the question which portion in the market does the production of centresexporters take during the transfer from one phase to another. The data obtained (under the conditions of sufficient number of such kind of observations published) can be used to make the next step in study of ancient Greek trade in the Black sea north region. it will be the development of economic and geographic division into regions based on quantitative indexes of import arrivals.